Sh. Virtual reallik texnologiyalari va musiqa terapiyasining terapevtik imkoniyatlari (SCIENCE and SOCIETY, 2026)
This article examines the theoretical aspects of integrating virtual reality technologies and music therapy and analyzes their impact on psychological well-being, emotional stability, and rehabilitation processes. The study demonstrates that music-based interventions in immersive virtual environments can effectively reduce stress and enhance therapeutic outcomes. The combined effects of virtual reality and music therapy are discussed.